Wound healing properties of a fibrin-based dermal replacement scaffold. (21st December 2021) - Brown, Stuart J; Surti, Farhana; Sibbons, Paul; Hook, Lilian
Abstract: When serious cutaneous injury occurs, the innate wound healing process attempts to restore the skin's appearance and function. Wound healing outcome is affected by factors such as contraction, revascularisation, regeneration versus fibrosis and re-epithelialisation and is also strongly influenced by the pattern and extent of damage to the dermal layer. Dermal replacement scaffolds have been designed to substitute for lost tissue, provide a structure to promote dermal regeneration, and aid skin grafting, resulting in a superior healing outcome. In this study the wound healing properties of a novel fibrin-alginate dermal scaffold were assessed in the porcine wound healing model and also compared to two widely used dermal scaffolds and grafting alone. The fibrin-alginate scaffold, unlike the other scaffolds tested, is not used in combination with an overlying skin graft. Fibrin scaffold treated wounds showed increased, sustained superficial blood flow and reduced contraction during early healing while showing comparable wound closure, re-epithelialisation and final wound outcome to other treatments. The increase in early wound vascularisation coupled with a decrease in contraction and no requirement for a skin graft suggest that the fibrin-based scaffold could provide an effective, distinctive treatment option to improve healing outcomes in human patients.